5, 6, 7 trihydroxy flavone armoured neurodegeneration caused by Quinolinic acid induced huntington's like disease in rat striatum - reinstating the level of brain neurotrophins with special reference to cognitive-socio behaviour, biochemical and histopathological aspects. (January 2022) - Purushothaman, Bhagyalakshmi; Sumathi, Thangarajan
Highlights: Baicalein attenuates motor-cognitive abnormalities of QA induced striatal lesion. Brain neurotrophins levels were augmented after baicalein administration. QA reverses GABAergic inhibition studied via TH immunohistochemical analysis. Baicalein restrained the antioxidant disturbance due QA lesion in striatal region. Abstract: Huntington Disease (HD), a predominant Neurodegenerative Disorder which might be induced by endogenous neurotoxin called Quinolinic Acid (QA), an N-methyl-D aspartate receptor (NMDAR) agonist, the bilaterally intrastriatal administration (200 nm/2 μL of saline) offers rise to the toxic events like neuronal death, neuroinflammation by inflicting excitotoxicity and oxidative stress in the striatum of male Wistar rats by exhibiting the behavioural changes which was accessed by rotarod, open field analysis. In this study, the neuropharmacological effect of Baicalein (BC) against QA induced HD was evaluated. Baicalein (BC), scientifically 5, 6, 7 trihydroxy flavone present naturally in the edible plants like Scutellaria baicalensis and Oroxylum indicum possess a better neuroprotective effect in the dosage of 10 mg/kg and 30 mg/kg intraperitoneally in the striatum of HD induced rats. This study proved that BC is efficient to revive the level of enzymatic & non-enzymatic antioxidants and mitochondrial complexes by decreasing the number of inflammatory mediators such as MDA, protein carbonyls and Nitric Oxide at the significance of P < 0.01 and restores the amount of BDNF and GDNF thereby preventing the neurophysiological changes which were analysed by haematoxylin & eosin staining. Thus finally, the protective effect of Baicalein displays the up-gradation of psychological and behavioural changes induced by QA.